Formulasi Sediaan Sabun Cuci Tangan Ekstrak Jeruk Nipis (Citrus aurantifolia) dan Efektivitasnya sebagai Antiseptik - Nikmatul Ikhrom Eka Jayani; Kartini Kartini; Nurul Basirah (MPI (Media Pharmaceutica Indonesiana), 2017)
Citrus aurantifolia (lime) is the natural ingredients having potential activity as an antiseptic. Thisstudy aimed to formulate a hand wash liquid soap with active ingredients lime juice and to evaluate its antisepticactivity. Three different formulas (Formula I, Formula II, and Formula III, with a concentration of lime juice 20,30, and 40%, respectively) were evaluated for their pH, visual appearance, density, and viscosity. Antiseptic activitytest was carried out using the replica method. The result showed that lime juice hand wash soap had a transparent,homogen, pale yellow color, and lime odor. Viscosity and pH of the preparation did not meet the criteriaof SNI (National Standart of Indonesia). Moreover, the results showed that an increased of lime juice concentrationimplied a significant decrease in viscosity and pH of the lime juice hand wash. Antiseptic activity test was indicatedby the percentage of bacterial reduction. The percentage of bacterial reduction for Formula I, II, and IIIwere 61.25, 68.89, and 89.06%, respectively. Statistical evaluation using one-way Anova (α = 0.05) followed byLSD showed the percentage of bacterial reduction in three formulas were significantly different compared tothe control formula (percentage of bacterial reduction = 35.8%). However, when the result were comparedto the positive control (percentage of bacterial reduction = 71.79%), there was no significant difference.